Investigating the regulatory effect of Shen Qi Bu Qi powder on the gastrointestinal flora and serum metabolites in calves - Yang, Haochi; Ren, Jianming; Ji, Peng; Zhang, Xiaosong; Mai, Zhanhai; Li, Chenchen; Zhao, Nianshou; Ma, Ting; Zhu, Xiaopeng; Hua, Yongli; Wei, Yanming (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectTo investigate the effects of Shen Qi Bu Qi Powder (SQBQP) on the average daily gain, blood indexes, gastrointestinal microflora, and serum metabolites of calves.MethodsA total of 105 calves were randomly assigned to three groups (n = 35 per group): the control group (C, fed with a basal diet for 21 days) and two treatment groups (SQBQP-L and SQBQP-H, fed with the basal diet supplemented with 15 and 30 g/kg of SQBQP), respectively for 21 days. The active components of SQBQP were identified using LC-MS/MS. Serum digestive enzymes and antioxidant indices were determined by ELISA kits and biochemical kits, respectively. Serum differential metabolites were analyzed by liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS), while flora in rumen fluid and fecal were analyzed by 16S rDNA sequencing. Further correlation analysis of gastrointestinal flora and serum metabolites of SQBQP-H and C groups were performed with Spearman’s correlation.ResultsThe principal active components of SQBQP mainly includes polysaccharides, flavonoids, and organic acids. Compared to the control group (C), calves in the SQBQP-H (high dose) and SQBQP-L (low dose) groups showed a significant increase in serum amylase (AMS) levels (P<0.001), while lipase content significantly decreased (P<0.05). Additionally, the average daily gain, T-AOC, and cellulase content of calves in the SQBQP-H group significantly increased (P<0.05). Proteobacteria and Succinivibrio in the rumen flora of the SQBQP-H group was significantly lower than that of the C group (P<0.05). The relative abundance of Proteobacteria, Actinobacteria, Candidatus_Saccharibacteria, Deinococcus_Thermus, Cyanobacteria, and Succinivibrio in the SQBQP-H group was significantly increased (P<0.05), while the relative abundance of Tenericutes and Oscillibacter was significantly decreased (P<0.05). Serum metabolomics analysis revealed 20 differential metabolites, mainly enriched in amino acid biosynthesis, β-alanine metabolism, tyrosine, and tryptophan biosynthesis metabolic pathways (P<0.05). Correlation analysis results showed that Butyrivibrio in rumen flora and Oscillibacter_valericigenes in intestinal flora were significantly positively correlated with average daily gain, serum biochemical indexes, and differential metabolite (-)-Epigallocatechin (R>0.58, P<0.05).ConclusionSQBQP can promote calves weight gain and enhance health by modulating gastrointestinal flora and metabolic processes in the body.